2021
DOI: 10.1101/2021.04.12.439584
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Formins play important role inLeishmaniaphysiology by acting as cytosolic actin bundlers

Abstract: Formin proteins regulate actin dynamics, are conserved throughout the eukaryotes cells. They play an important role in cell adhesion, motility, vesicular trafficking, and cytokinesis. Formins from class Kinetoplastida which includes infective organisms such as Leishmania and Trypanosoma not characterized to date, even though they are shown to be important in other protozoan parasites. The protozoan parasite Leishmania major (Lm) has two homologous formin proteins; LmForminA and LmForminB. Our study showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 83 publications
0
0
0
Order By: Relevance
“…It has been shown that the transcription of this gene and, subsequently, glycolysis is significantly increased in Leishmania infection [80]. DIAPH1 has roles in cell adhesion, motility, vesicular trafficking, and cytokinesis [81]. Meanwhile, BIRC3 and ATF3 are involved in apoptosis and immunity, respectively.…”
Section: And Table B In S1 Data)mentioning
confidence: 99%
“…It has been shown that the transcription of this gene and, subsequently, glycolysis is significantly increased in Leishmania infection [80]. DIAPH1 has roles in cell adhesion, motility, vesicular trafficking, and cytokinesis [81]. Meanwhile, BIRC3 and ATF3 are involved in apoptosis and immunity, respectively.…”
Section: And Table B In S1 Data)mentioning
confidence: 99%